The Nexus of AI Ethics, Mobile Learning, and Sustainable Development Goals in Higher Education: The Mediating Role of Law-Compliant Strategies - Zemlyak, Svetlana; Galina Khromenkova; Olga Gusarova (International Journal of Interactive Mobile Technologies (iJIM), 2026)
This study investigated the relationships among perceived AI ethical concerns, mobile learning adoption, law-compliant strategy, and integration of the Sustainable Development Goals (SDGs) in higher education, with technology readiness as a moderating variable. A quantitative cross-sectional survey was administered to 370 university students experienced with artificial intelligence (AI)-based educational tools and mobile learning platforms. Data analysis employed SPSS and partial least squares structural equation modelling (PLS-SEM). Results indicated that perceived AI ethical concerns (β = 0.42, p < 0.001) and mobile learning adoption (β = 0.31, p < 0.001) significantly influenced law-compliant strategy, which strongly predicted SDG integration (β = 0.48, p < 0.001). Law-compliant strategy mediated the relationship between ethical concerns and sustainability outcomes (β = 0.20, p < 0.001). The direct effect of technology readiness on sustainability was not significant (β = 0.09, p = 0.072), and law-compliant strategy did not mediate the mobile learning sustainability relationship (β = 0.08, p = 0.110). Technology readiness significantly moderated the relationship between law-compliant strategy and sustainability (β = 0.14, p < 0.001). The model accounted for 46% of the variance in SDG integration. These findings highlight the need for robust, law-compliant governance frameworks to translate ethical awareness and technology adoption into sustainable development outcomes. The study demonstrates that law-compliant strategies are essential mechanisms linking ethics-aware AI systems and mobile learning to sustainable development.